1995
DOI: 10.1136/hrt.73.5.434
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral haemodynamic effects of inhibition of prostaglandin synthesis in congestive heart failure and interactions with captopril.

Abstract: Objectives-To investigate the role of prostaglandins in maintaining circulatory homoeostasis in chronic heart failure and the hypothesis that an increase in vasodilatory prostaglandin synthesis may contribute to the actions of angiotensin converting enzyme inhibitors in heart failure. Design-Randomised, double blind, placebo controlled studies. Cardiac output and renal and limb blood flow were measured after oral indomethacin 50 mg or placebo followed by "open" intravenous infusion of prostaglandin E, (study A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
0
40
1
Order By: Relevance
“…14 Conversely, in a more recent study in humans, indomethacin caused adverse hemodynamic and renal effects. 15 To clarify this question, we used a mouse model of drug-induced heart failure to test the hypothesis that the progression of heart failure can be attenuated by selective COX-2 inhibition after initial injury and that this may have a beneficial effect on cardiac function and mortality.…”
mentioning
confidence: 99%
“…14 Conversely, in a more recent study in humans, indomethacin caused adverse hemodynamic and renal effects. 15 To clarify this question, we used a mouse model of drug-induced heart failure to test the hypothesis that the progression of heart failure can be attenuated by selective COX-2 inhibition after initial injury and that this may have a beneficial effect on cardiac function and mortality.…”
mentioning
confidence: 99%
“…38 In CHF, NSAIDs' deleterious effects are more predominant, since PG and bradykinin are stimulated in order to counteract water retention and vasoconstriction. Indeed, administration of NSAIDs results in decreased renal plasma flow and glomerular filtration rate, 18,39 and adversely affects cardiac index, left ventricular filling pressure and systemic vascular resistance, particularly in hyponatraemic patients. 4,8,18 Townend et al demonstrated that this deleterious effect was…”
Section: Negative Effects Of Nsaids Including High-dose Aspirinmentioning
confidence: 99%
“…16,18 These PGs have both vasodilatator (PGE2 and PGI2) and vasoconstrictor properties (PGH2 and TxA2), but the overall effect of COX blockade is an increase in systemic vascular resistance, which may result in a reduction in organ perfusion. 18 Bradykinin also has cardioprotective effects and the removal of bradykinin receptors in mice results in hypertension, left ventricular remodelling and functional impairment.…”
Section: Theoretical Background For An Interaction Between Cyclooxygementioning
confidence: 99%
See 2 more Smart Citations